1990
DOI: 10.1126/science.1701274
|View full text |Cite
|
Sign up to set email alerts
|

ELAM-1 Mediates Cell Adhesion by Recognition of a Carbohydrate Ligand, Sialyl-Le x

Abstract: Recruitment of neutrophils to sites of inflammation is mediated in part by endothelial leukocyte adhesion molecule-1 (ELAM-1), which is expressed on activated endothelial cells of the blood vessel walls. ELAM-1 is a member of the LEC-CAM or selectin family of adhesion molecules that contain a lectin motif thought to recognize carbohydrate ligands. In this report, cell adhesion by ELAM-1 is shown to be mediated by a carbohydrate ligand, sialyl-Lewis X (SLex; NeuAc alpha 2,3Gal beta 1,4(Fuc alpha 1,3)-GlcNAc-), … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

7
510
0
6

Year Published

1995
1995
2002
2002

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 1,290 publications
(523 citation statements)
references
References 44 publications
7
510
0
6
Order By: Relevance
“…Phillips et al (1990) demonstrated that anti-sL x CSLEX mAb blocked adhesion of a human promyelocytic cell line to human endothelial cells. These results indicated the complexity of expression and function of sL x and sL a epitopes on the established cell lines.…”
Section: Clinicalmentioning
confidence: 99%
See 1 more Smart Citation
“…Phillips et al (1990) demonstrated that anti-sL x CSLEX mAb blocked adhesion of a human promyelocytic cell line to human endothelial cells. These results indicated the complexity of expression and function of sL x and sL a epitopes on the established cell lines.…”
Section: Clinicalmentioning
confidence: 99%
“…Such findings were not known when we had planned this prospective randomized control study. But now, it is known that sialyl Lewis-X (sL x ) and sialyl Lewis-A (sL a ) antigens are ligands to Eselectin, and sL x and sL a expressed on cancer cells mediate adhesion of the cancer cells to vascular endothelial cells expressing Eselectin (Phillips et al, 1990;Takada et al, 1991Takada et al, , 1993. The adhesion of cancer cells to vascular endothelial cells is a key step in invasion and metastasis of cancer cells (Hoff et al, 1989(Hoff et al, , 1990Nakamori et al, 1993).…”
mentioning
confidence: 99%
“…Endothelial cell surface ICAM-1 is one of the ligands for neutrophil CD11/CD18, and mediates CD11/CD18-dependent adhesion to endothelium [18,29,30]. E-selectin recognizes Sialy-Lewis X, which is another neutrophil ligand [31]. Adhesion of neutrophils to E-selectin increases its CD11/CD18 expression, which in turn augments adhesion of neutrophils to endothelium [32].…”
Section: Discussionmentioning
confidence: 99%
“…Expression of E-selectin is induced on the cell surface of activated endothelial cells by key mediators of inflammation such as Il-1b and TNF-a (Bevilacqua et al, 1987) and has also been reported on the surface of tumour endothelial cells (Ye et al, 1995). Cell adhesion to E-selectin is mediated through the carbohydrate ligands sL X and sL A which are expressed predominantly on neutrophils (Phillips et al, 1990). In this way neutrophils can be recruited to sites of inflammation.…”
mentioning
confidence: 95%